The Impact of Entrepreneurship Education in High School on Long-Term Entrepreneurial Performance - Niklas Elert; Fredrik Andersson; Karl Wennberg (Research Institute of Industrial Economics (IFN), 2015)
This paper studies the long-term impact of entrepreneurship education and training in high school on entrepreneurial entry, performance, and survival. Using propensity score matching, we compare three Swedish cohorts from Junior Achievement Company Program (JACP) alumni with a matched sample of similar individuals and follow these for up to 16 years after graduation. We find that while JACP participation increases the long-term probability of starting a firm as well as entrepreneurial incomes, there is no effect on firm survival.
Keywords: D22; L25; L26; 330; Entrepreneurship Education; Quasi-experiment; Performance